Utilização de resíduo vegetal do chuchu (Sechium edule SW.) como coagulante natural para tratamento de efluentes têxteis - Almeida, Cibele Andrade de (2015)
This study aimed to evaluate the efficiency of aqueous extract of plant residue of chayote (Sechium edule SW.) As a natural coagulant in the treatment of textile effluents, using coagulation / flocculation technique. The effect of pH, FeCl3 dosage and dosage of the aqueous extract of the vegetable residue at chayote turbidity and chemical oxygen demand (COD) were investigate by testing jars by the standard test method. The optimization process of the treatment of textile effluent was conducted by response surface methodology (RSM) based on experimental design Box-Behnken, and the variables under study: FeCl3 dosage, dosage of plant residue extract chayote and pH, having as a percentage of the response to turbidity and COD. The characterization of the vegetable residue by chayote spectroscopy analysis by Fourier Transform Infrared (FTIR) spectra and 13C nuclear magnetic resonance solid (13C NMR / CPMAS) indicated that the residue showed absorption bands and typical signs of polysaccharides in case characteristic of anionic polyelectrolytes. As satisfying the conditions set by the experimental design were dosage FeCl3 = 47.40 mg L-1 dosage aqueous extract of plant residue chayote = 15.00 mg L-1 and pH = 6.14 obtaining removing percentage Turbidity and COD of 97.95% and 83.84% respectively. The results showed that the aqueous extract of chayote proved to be a natural coagulant potential, but this has greater efficiency when associated with a low dosage of FeCl3, with better performance as flocculation aid. Through this association was observe a 75% reduction of the FeCl3 dosage, indicating that the addition of the extract has improved the process efficiency by using a minimum dosage of FeCl3